1992
DOI: 10.1002/1097-0142(19920601)69:11<2623::aid-cncr2820691102>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated glycoprotein distribution detected by monoclonal antibody B72.3 in salivary neoplasia

Abstract: The expression of tumor‐associated glycoprotein (TAG‐72), an oncofetal mucin‐like tumor‐associated glycoprotein derived from membrane‐enriched fractions of metastatyic breast carcinoma, has been detected by monoclonal antibody (MoAb) B72.3 in adenocarcinomas of breast, colon, lung, endometrium, pancreas, and ovary. The authors reported the scope of TAG‐72 expression detected by MoAb B72.3 in salivary neoplasia. They examined 96 salivary lesions (53 malignant and 37 benign primary tumors, 2 metastatic carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…TAG-72 was also found to be expressed by oral cancer cells (18, 21), indicating that hcc49scFv-FasL, possibly through binding to TAG-72, induced FasL-mediated cell death (Fig. 3A).…”
Section: Resultsmentioning
confidence: 93%
“…TAG-72 was also found to be expressed by oral cancer cells (18, 21), indicating that hcc49scFv-FasL, possibly through binding to TAG-72, induced FasL-mediated cell death (Fig. 3A).…”
Section: Resultsmentioning
confidence: 93%
“…It was proposed that the Mab B72.3 can be used to define TAG‐72 expression in many adenocarcinomas and may serve as an adjunctive tool for the diagnosis and histologic typing of malignant cells in fine‐needle aspiration biopsy specimens 4 . Brandwein et al 10 examined many tumors of salivary glands using the Mab B72.3 and found diffuse expression of TAG‐72 in mucoepidermoid carcinoma, squamous carcinoma, Wharthin's tumor and papillary cystadenoma. They suggested that as the diffuse expression of TAG‐72 does not occur only in malignant tumors, the TAG‐72 expression in fineneedle aspiration biopsies must be interpreted with caution to serve as a diagnostic aid.…”
Section: Discussionmentioning
confidence: 99%
“…TAG‐72 expression was categorized as diffuse, focal, or negative according to Brandwein et al 10 Diffuse pattern of staining was defined as 1 or more low‐power fields (10 ×) of positive cells. Focal pattern of staining was defined as a few positive cells or groups of cells seen at high‐power magnification (40 ×).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] In select cases the immunophenotype of the neoplasm may be extremely useful in determining the correct diagnosis and predicting prognosis. 8,9 Currently, work is under way to clarify the pathogenesis of these tumors, to identify factors that modulate the direction and extent of differentiation, and to predict their clinical behavior and/or response to treatment. Developments in monoclonal antibody (Mab) technology have offered an opportunity to expand our knowledge of the cellular and subcellular events that produce human disease.…”
mentioning
confidence: 99%